Growth hormone and aging: A challenging controversy - Andrzej Bartke (Dove Medical Press, 2008)
Andrzej BartkeGeriatrics Research, Departments of Internal Medicine and Physiology, Southern Illinois University School of Medicine, Springfield, IL, USAAbstract: Although advanced age or symptoms of aging are not among approved indications for growth hormone (GH) therapy, recombinant human GH (rhGH) and various GH-related products are aggressively promoted as anti-aging therapies. Well-controlled studies of the effects of rhGH treatment in endocrinologically normal elderly subjects report some improvements in body composition and a number of undesirable side effects in sharp contrast to major benefits of GH therapy in patients with GH deficiency. Controversies surrounding the potential utility of GH in treatment of a geriatric patient are fueled by increasing evidence linking GH and cancer and by remarkably increased lifespan of GH-resistant and GH-deficient mice. Conservation of cellular signaling mechanisms that influence aging in organisms ranging from worms to mammals suggests that at least some of the results obtained in mutant mice are applicable to the human. We suggest that the normal, physiological functions of GH in promoting growth, sexual maturation and fecundity involve significant costs in  terms of aging and life expectancy. Natural decline in GH levels during aging likely contributes to concomitant alterations in body composition and vigor but also may be offering important protection from cancer and other age-associated diseases.Keywords: growth hormone, longevity, cancer, anti-aging therapies, mutant mice